Quality assisted living : informing practice through research - Morgan, Leslie A. (New York : Springer Pub., 2012)
All 50 states currently regulate assisted living facilities in order to minimized safety risks and guarantee a basic set of rights and services to residents. What has not been adequately addressed, however, is the need to create, sustain, and evaluate quality of life in these settings. Quality Assisted Living provides results from a 4-year National Institute on Aging-funded study that gathered extensive information not only from residents, but also from staff and family members. This book focuses on what people, particularly the residents, mean when they discuss the ambiguous concept of quality. This volume addresses the complexities underlying seemingly clear-cut issues and provides concrete suggestions for re framing problems in order to find better solutions.--[book cover]
Includes bibliographical references and index.
Keywords: Old age homes; Nursing Homes; Congregate housing; Older people -- Care